Kajian Fenomenologi Pada Pengalaman Auditor Internal di Kementerian X Dalam Melaksanakan Audit - Nur Sanny Rahmawati; Laksmi Laksmi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
This study discusses the auditors’ experiences in carrying out audits. The aim of this study is to identify the auditors’ experiences in carrying out internal audits at Ministry X. This study uses qualitative approach with the phenomenological method. The data collection technique used in this research are observation and interview with 4 (four) auditors with different level of expertise. Based on the research results, the experiences of the four auditors in carrying out audits at Ministry X is interpreted as an awareness based on things that support their profession, such as practice and knowledge which is gained from their past education. This awareness also grows their integrity and objectivity as an auditor. The awareness also makes an intersubjectivity that is built from good relations between the fellow auditors, the leader, and the auditees. This supports the four auditors to act professionally and accountably during working time and friendly when out of working hours.